Nucleophilic Ring Opening of Donor–Acceptor Cyclopropanes with the Cyanate Ion: Access to Spiro[pyrrolidone-3,3′-oxindoles] - Zaytsev, Sergey V; Ivanov, Konstantin L; Skvortsov, Dmitry A; Bezzubov, Stanislav I; Melnikov, Mikhail Ya; Budynina, Ekaterina M (Journal of organic chemistry, 2018)
The nucleophilic ring opening of donor–acceptor cyclopropanes with the cyanate ion is reported for the first time. Cyclopropanes, spiro-activated with oxindole fragments as acceptors, are shown to undergo transformations into biologically relevant spiro[pyrrolidone-3,3′-oxindoles] while being treated with potassium cyanate under microwave assistance.